A multi-criteria framework for enhancing decision-making in the risk management strategies of a global IT project - Nicoleta-Madalina Stan; Constantin Dorin Olteanu; Aurel Mihail Titu (Journal of Research and Innovation for Sustainable Society)
In the dynamic landscape of global Information Technology (IT) projects, effective risk management is paramount for ensuring project success and mitigating potential disruptions. As organizations increasingly rely on IT to drive their business initiatives, the complexity and interconnectedness of global IT projects demand a systematic approach to risk management. The proposed framework integrates various criteria, including but not limited to financial impact, technological complexity, regulatory compliance, and geopolitical factors. By considering these diverse aspects, the framework provides a holistic view of potential risks, allowing project managers and stakeholders to make informed decisions. The integration of multiple criteria ensures that the framework captures the intricacies of global IT projects, addressing both tangible and intangible aspects of risk. The framework also leverages sophisticated analytics and modeling methods to evaluate the likelihood and consequences of identified risks. This allows project teams to rank risks by their potential impact, facilitating resource allocation and the creation of specific mitigation plans. Its dynamic nature ensures it can adapt to changing project environments, allowing for real-time updates to risk management strategies as new data emerges. Case studies and simulations showcase the framework’s effectiveness in enhancing decisionmaking processes for global IT projects. The outcomes highlight the framework's ability to enhance risk visibility, optimize resource allocation, and ultimately contribute to the successful delivery of IT projects on a global scale. The integration of this framework into existing project management practices empowers organizations to proactively manage risks and navigate the intricate challenges associated with large-scale, global IT initiatives